The epidemiology of stillbirths according to the perinatal problems identification program (PPIPP), at Rahima Moosa Mother and Child Hospital, from August 2016 to July 2017 - Onwuagbu, Oburota Uchenna (My University, 2020)
Background The occurrence of stillbirth is an adverse outcome of pregnancy that could reflect the quality of antenatal and intrapartum care that pregnant women receive. Some stillbirths can be averted by addressing avoidable risk factors. Methods A retrospective, observational study was undertaken at Rahima Moosa Mother and Child Hospital (RMMCH). This is a regional academic hospital located in Coronationville, Johannesburg, South Africa. At RMMCH approximately thirteen thousand deliveries occur annually. This study reviewed medical records of women who delivered stillbirths weighing more than 500g from August 2016 to July 2017. Avoidable attributable factors as well as obstetrical causes of stillbirth were evaluated for each case using the third version of the perinatal problems identification program (PPIP v3). The stillbirth rate was calculated for the time period of August 2016 to July 2017. A five year trend in the stillbirth rate was also calculated for the period of 2011 to 2015. The stillbirth rate amongst non-South African citizens was also ascertained.Results A total of 206 medical records of women who delivered stillbirths were reviewed. The stillbirth rate was 21.9/1 000 births for the time period of August 2016 to July 2017; which was higher than observed in the preceding five years, between 2011 to 2015 (12.0/1 000). For the study-period, most stillbirths (71.9%) were late foetal deaths (LFD). The stillbirth rate between South African and non-South African citizens was similar at 13.7 and 14.8 per 1000 birth rate, respectively. In terms of maternal conditions, 62.6% of women in this study were healthy mothers. The leading cause of death (35.4%) were macerated stillbirths with unexplained intrauterine foetal death. The main avoidable risk factor was a delay in seeking medical attention in 125 cases (60.7%); being possible in 74 (35.9%) and probable in 51 (24.7%). Among administrative related avoidable factors, a lack of transport from home to institution was evaluated as a contributing factor in 167 cases (72.3%); being possible in 128 (62.1%) and probable in 39 (10.2%). No medical response to poor fundal growth by a medical personnel was possible in 5 cases (2.4%) and probable in 16 (7.8%) with regard to health worker related avoidable factors. Placental histological analysis (190/206; 92.2%) showed that up to 40% of placentae showed vascular flow compromise, 13.6% displaying infection v and 6.3% displaying a combination of the two. There was a statistically significant association between abnormal placental findings and stillbirths (p<0.001). Conclusion Most stillbirths evaluated in this study could have been averted if there was more timeous health seeking behaviour, improved logistical issues related to transport to the hospital, and better antenatal care in monitoring for adequate fundal growth were addressed. There is a strong correlation between stillbirths and abnormal placental pathologies.
A research report submitted in partial fulfilment of the requirements for the degree of Masters of Medicine in Obstetrics and Gynaecology to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, 2020